Strategic planning objectives for venture capitalist investments in emerging information technologies: A value-focused perspective - David L. Coss; Gupreet Dhillon; Ifeoma Udeh (The Journal of Entrepreneurial Finance (JEF), 2015)
Academic and practitioner literature suggests that Venture Capitalists often have problems with aligning information technology opportunities with investment objectives. To a large extent the alignment process is not formally documented and relies on intuitive instincts. Hence it is important to define Venture Capitalist objectives for investments in emerging information technologies. This paper uses the Value-Focused Thinking approach to identify, define and structure value driven objectives. Based on data collected from a number of Venture Capitalist interviews we identified 130 values, which resulted in 72 objectives. These objectives were organized into 22 clusters, which were bifurcated into fundamental and means categories. In a final synthesis we present a 7 fundamental and 15 means categorical objectives for strategically planning Venture Capitalist investments in emerging information technologies.
Keywords: G24; O32; M13; 650; strategic planning; Venture Capitalists; emerging information technologies; value-focused thinking